Improving Shooting Accuracy In Football Through Paired Wall-Pass Training Method (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of paired wall-pass training on improving shooting accuracy in soccer among students at SDN Cinta Asih. The research employed an experimental method with a One-Group Pretest-Posttest Design. The subjects were 16 male students participating in extracurricular soccer activities. Data were collected using a shooting accuracy test consisting of 10 attempts at the goal. The training program was conducted over 14 sessions with a frequency of three times per week. The analysis results indicated a significant improvement between the pretest scores (mean = 18.4) and posttest scores (mean = 32.8), with a t-value of 12.240 > t-table 2.160 and p < 0.05. Regression analysis showed that paired wall-pass training contributed 7% to the improvement in shooting accuracy. The study concludes that the paired wall-pass training method is effective in enhancing the shooting skills of elementary school students.